(Re)defining nursing leadership: On the importance of parrhèsia and subversion. (24th November 2021) - Jenkins, Danisha; Burton, Candace; Holmes, Dave
Abstract: Aim: Through a review of philosophical and theoretical constructs, this paper offers insight and guidance as to ways in which nurse leaders may operationalize advocacy and an adherence to nursing's core ethical values. Background: The US health care system works in opposition to core nursing values. Nurse leaders are obliged to advocate for the preservation of ethical care delivery. Evaluation: This paper draws upon the philosophies of Fromm, Foucault, and Deleuze and Guattari to critically review the functions of nurse leaders within a capitalist paradigm. Key issue: Key emergent issues in the paper include health care and capitalism and the nurse leader's obligations towards advocacy. Conclusion: The nurse leader acts as parrhèsia in viewing truth telling as a duty critical to improving the lives of patients. Ramifications of the decisions by those in power have even greater impact in institutions that serve those with little to no political agency. Implications for Nursing Management: The nurse leader has a freedom and platform that their patients do not and must take the courageous risk of choosing to speak. This paper serves as a call to action for nurse leaders to urgently address the current state of US health outcomes.